2001
DOI: 10.1046/j.1442-9071.2001.d01-29.x
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis in Herpes zoster ophthalmicus

Abstract: In this study, most patients were immunocompetent individuals. The course of the uveitis was generally uniphasic in nature and of a relatively short duration. There was a high incidence of secondary glaucoma with 15% of all patients requiring surgical intervention. The visual loss in the five patients was not directly related to the uveitis and secondary glaucoma but to other complications associated with HZO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 11 publications
2
18
0
3
Order By: Relevance
“…The literature further confirms that glaucoma occurs more commonly in granulomatous uveitis and in association with entities such as Fuchs heterochromic cyclitis or herpes. 5,[13][14][15][16] The distribution of the anatomic localization of uveitis in our study, where most cases occurred in the anterior part (adults 53, children 67%), is in accordance with others studies, which reported an anterior location in 68% of patients. 5 In our group, every patient received topical therapy at least temporarily.…”
Section: Discussionsupporting
confidence: 94%
“…The literature further confirms that glaucoma occurs more commonly in granulomatous uveitis and in association with entities such as Fuchs heterochromic cyclitis or herpes. 5,[13][14][15][16] The distribution of the anatomic localization of uveitis in our study, where most cases occurred in the anterior part (adults 53, children 67%), is in accordance with others studies, which reported an anterior location in 68% of patients. 5 In our group, every patient received topical therapy at least temporarily.…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the occurrence of uveitis showed a significant association with subsequent visual loss. Early identification and treatment are all the more important as uveitis in HZO is amenable to steroid therapy 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…4 Hutchinson's sign is defined as skin lesions at the tip, side, or root of the nose and is a strong predictor of ocular inflammation and corneal denervation in HZO, especially if both branches of the nasociliary nerve are involved. 5,6 A study by Thean et al 7 identified the clinical features of uveitis secondary to HZO. Most patients were immunocompetent.…”
Section: Herpes Zoster Ophthalmicus and Glaucomamentioning
confidence: 98%